Preinvasive Colorectal Lesions of African Americans Display an Immunosuppressive Signature Compared to Caucasian Americans - Wallace, Kristin; Nahhas, Georges J.; Bookhout, Christine; Lewin, David N.; Paulos, Chrystal M.; Nikolaishvili-Feinberg, Nana; Cohen, Stephanie M.; Guglietta, Silvia; Bakhtiari, Ali; Camp, E. Ramsay; Hill, Elizabeth G.; Baron, John A.; et al. (Frontiers in Oncology, 2021)
Background: African Americans (AAs) have higher colorectal cancer (CRC) incidence and mortality rate than Caucasian Americans (CAs). Recent studies suggest that immune responses within CRCs contribute to the disparities. If racially distinct immune signatures are present in the early phases of carcinogenesis, they could be used to develop interventions to prevent or slow disease. Methods: We selected a convenience sample of 95 patients (48 CAs, 47 AAs) with preinvasive colorectal adenomas from the surgical pathology laboratory at the Medical University of South Carolina. Using immunofluorescent-conjugated antibodies on tissue slides from the lesions, we quantified specific immune cell populations: mast cells (CD117+), Th17 cells (CD4+RORC+), and NK cell ligand (MICA/B) and inflammatory cytokines, including IL-6, IL-17A, and IFN-𝛾. We compared the mean density counts (MDCs) and density rate ratios (RR) and 95% CI of immune markers between AAs to CAs using negative binomial regression analysis. We adjusted our models for age, sex, clinicopathologic characteristics (histology, location, dysplasia), and batch. Results: We observed no racial differences in age or sex at the baseline endoscopic exam. AAs compared to CAs had a higher prevalence of proximal adenomas (66% vs. 40%) and a lower prevalence of rectal adenomas (11% vs. 23%) (p =0.04) but no other differences in pathologic characteristics. In age, sex, and batch adjusted models, AAs vs. CAs had lower RRs for cells labeled with IFN𝛾 (RR 0.50 (95% CI 0.32-0.81); p=0.004) and NK cell ligand (RR 0.67 (0.43-1.04); p=0.07). In models adjusted for age, sex, and clinicopathologic variables, AAs had reduced RRs relative to CAs for CD4 (p=0.02), NK cell ligands (p=0.01), Th17 (p=0.005), mast cells (p=0.04) and IFN-𝛾 (p< 0.0001). Conclusions: Overall, the lower RRs in AAs vs. CAs suggests reduced effector response capacity and an immunosuppressive (‘cold’) tumor environment. Our results also highlight the importance of colonic location of the adenoma in influencing these differences; the reduced immune responses in AAs relative to CAs may indicate impaired immune surveillance in early carcinogenesis. Future studies are needed to understand the role of risk factors (such as obesity) in influencing differences in immune responses by race.